Recovery by N-acetylcysteine from subchronic exposure to Imidacloprid-induced hypothalamic–pituitary–adrenal (HPA) axis tissues injury in male rats. (2nd September 2015) - Annabi, Alya; Dhouib, Ines Bini; Lamine, Aicha Jrad; Golli, Nargès El; Gharbi, Najoua; Fazâa, Saloua El; Lasram, Mohamed Montassar
Abstract: Imidacloprid is the most important example of the neonicotinoid insecticides known to target the nicotinic acetylcholine receptor in insects, and potentially in mammals. N -Acetyl-l -cysteine (NAC) has been shown to possess curative effects in experimental and clinical investigations. The present study was designed to evaluate the recovery effect of NAC against Imidacloprid-induced oxidative stress and cholinergic transmission alteration in hypothalamic–pituitary–adrenal (HPA) axis of male rats following subchronic exposure. About 40 mg/kg of Imidacloprid was administered daily by intragastric intubation and 28 days later, the rats were sacrificed and HPA axis tissues were removed for different analyses. Imidacloprid increased adrenal relative weight and cholesterol level indicating an adaptive stage of the general alarm reaction to stress. Moreover, Imidacloprid caused a significant increase in malondialdehyde level, the antioxidants catalase, superoxide dismutase and glutathione- S -transferase showed various alterations following administration and significant depleted thiols content was only recorded in hypothalamic tissue. Furthermore, the hypothalamic and pituitary acetylcholinesterase activity and calcium level were significantly increased highlighting the alteration of cholinergic activity. The present findings revealed that HPA axis is a sensitive target to Imidacloprid (IMI). Interestingly, the use of NAC for only 7 days post-exposure to IMI showed a partial therapeutic effect against Imidacloprid toxicity.